2006
DOI: 10.1297/cpe.15.23
|View full text |Cite
|
Sign up to set email alerts
|

A Spectrum of Clinical Presentations in Seven Japanese Patients with Vitamin D Deficiency

Abstract: Recently, the reemergence of vitamin D deficiency in developed countries has been pointed out. Vitamin D deficiency is diagnosed based on the serum 25-hydroxyvitamin D (25OHD) level. However, its normal range is still controversial, making the diagnosis of vitamin D deficiency difficult. Here, we present seven Japanese patients diagnosed with vitamin D deficiency. Three patients complained of leg bowing, and the other four of tetany. The patients with leg bowing were toddlers. Radiographic surveys demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…Playing outside twice a week or less was regarded as insufficient sun exposure. Laboratory data without serum FGF23 levels of 3 DR patients and those with serum FGF23 levels of 2 HR patients were included in previous publications by our group [9,21]. Measurement of serum FGF23 levels was approved by the institutional review board of Osaka University Hospital and written informed consent was obtained from the parents or guardians of the patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Playing outside twice a week or less was regarded as insufficient sun exposure. Laboratory data without serum FGF23 levels of 3 DR patients and those with serum FGF23 levels of 2 HR patients were included in previous publications by our group [9,21]. Measurement of serum FGF23 levels was approved by the institutional review board of Osaka University Hospital and written informed consent was obtained from the parents or guardians of the patients.…”
Section: Methodsmentioning
confidence: 99%
“…Increased numbers of patients with vitamin D deficiency have been reported among children in recent years throughout the world [3,4,5], including Japan [6,7,8,9]. Circulating 25-hydroxyvitamin D [25(OH)D] concentration is the best clinical indicator of vitamin D repletion in the body.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety hyperventilation was correspondingly common in our study (13%) having overt tetany in 12 out of 14 patients and was predominant in females. Hypocalcemia and tetany by reason of VDD were similarly common [10] . Malnutrition, malabsorption disorders, for example, Celiac disease, decreased sunlight exposure and urbanization was associated with VDD [11] .…”
Section: Resultsmentioning
confidence: 99%
“…However, the present patient exhibited a normal level of serum phosphorus. It has been reported that patients with rickets due to vitamin D deficiency display normal to higher levels of serum phosphorus, suggesting that the absence of a low level of inorganic phosphorus is not necessary for a diagnosis of rickets (14).…”
Section: Discussionmentioning
confidence: 99%